The Laudare School : the quest for excellence in the inner-city - Truscott, Ashley; Bowen, Amanda; Cohn, Sid ([London] : SAGE, 2016)
In early January 2013, Adrian Miller, principal of the Laudare School, situated close to the inner-city in the lower-income suburb of Belmont in Johannesburg, was reading through the results of a recent customer satisfaction survey. While the feedback from parents and pupils was generally positive, it also highlighted some areas that needed attention, particularly the challenges of running a private school in an inner-city environment. Furthermore, with scarce resources it was difficult to grow and develop the school into one that offered an excellent educational experience. Miller wondered how he could ensure that the school offered its pupils, teachers, and parents a service that was in line with his vision.
Originally Published in: Truscott, A., Bowen, A., & Cohn, S. (2013). The Laudare School: The Quest for Excellence in the Inner-City. WBS-2013-11. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; Laudare School; Educational leadership -- South Africa -- Johannesburg -- Case studies; School management and organization -- South Africa -- Johannesburg -- Case studies; Relationship marketing -- Case studies